MODELING AND CONTROL OF MINI DISTILLATION COLUMN USING SLIDING MODE CONTROLLER - MAULIDDA (NIM : 23215069), RENNY
This thesis presents the model and control design of distillation process as a common component separation process in chemical operations. Mini distillation column for laboratory scale is used to separate ethanol and water components. Distillation process is carried out by charged the liquid components into the heater pot which is called batch process. Batch distillation column modeling is obtained by deriving mathematically the chemical and physical processes during the distillation process. Equations of modeling are expressed based on equilibrium component mass, vapor-liquid equilibrium (VLE) and other physical characteristics. From the derivation of mathematical equations, nonlinear system model is obtained. The model is simulated by MATLAB software and validated with data on real plant experiment. In this study, in order to design the sliding mode controller, a model of the identification system is built because the nonlinear inverse of the mathematical equations is undefined in the sliding mode controller. The experimental data in system identification is the water concentration data that represents the linear system. The identification result shows that the distillation column model has been appropriated with the experimental data response with 91.78% of fit percentage match. From the linear model, the simulation of sliding mode controller method is used by linear continuous feedback approach to produce the pure distillate of ethanol concentration by desired concentration, which is the output of the distillation system. The design of an observer for a closed loop system is used to estimate an unmeasured state variable. The results of the sliding mode control simulation show that the system is stable in closed loop system and has been able to follow the given reference.